A Directional Strain Sensor Based on Anisotropic Microhoneycomb Cellulose Nanofiber‐Carbon Nanotube Hybrid Aerogels Prepared by Unidirectional Freeze Drying. Issue 14 (1st March 2019) - Wang, Cong; Pan, Zheng‐Ze; Lv, Wei; Liu, Bilu; Wei, Jie; Lv, Xiaohui; Luo, Yi; Nishihara, Hirotomo; Yang, Quan‐Hong
Abstract: Aerogels are one of the most popular composite reinforcement materials because of their high porosity and their continuous and homogeneous network. Most aerogels are isotropic, thus leading to isotropic composites when they are used as fillers. This fundamentally limits their applications in areas where anisotropy is needed. Here, an anisotropic microhoneycomb cellulose nanofiber‐ (CellF)‐carbon nanotube (CNT) aerogel (denoted MCCA) is reported that contains unidirectionally aligned penetrating microchannels, which is prepared by a unidirectional freeze‐drying method, using the structure‐directing function of the CellFs. Due to its anisotropic nature, MCCA‐reinforced polydimethylsilexane (denoted MCCA/PDMS) shows distinct anisotropic behavior, with the electrical conductivity and Young's modulus along the direction of penetrating microchannels being approximately twice those in the orthogonal direction. MCCA/PDMS is used to make "directional" strain sensors with electrical resistance as the output signal. They demonstrate a 92% sensitivity difference between the microchannel direction and its orthogonal direction. This approach can be used to prepare anisotropic MCCA‐based composites with other polymers for different applications. Abstract : Anisotropic microhoneycomb cellulose nanofiber‐carbon nanotube aerogels (MCCAs) are prepared by unidirectional freeze drying and endow anisotropic electrical conductivity and Young's modulus to a MCCA/polydimethylsiloxane composite. Thus, it is utilized in directional strain sensors with dramatically different response along different directions, showing a new direction for anisotropic aerogel applications.